Implementasi Peraturan Daerah Pasaman Barat Nomor 9 Tahun 2017 Tentang Larangan Meminta Sumbangan di Jalan Raya Perspektif Siyāsah Dustūriyyah - Maiza; Harahap, Mhd. Yadi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The implementation of West Pasaman Regency Regional Regulation No. 9 of 2017 regarding the prohibition of soliciting donations on public roads has not been fully effective, as a clear gap remains between legal norms and community practices. Although the regulation aims to maintain public order and ensure road safety, roadside fundraising continues, especially for mosque construction and religious social activities. This study analyzes the implementation of Article 24 in Dusun binjai, Sungai Aur District, and examines the policy through the perspective of siyāsah dustūriyyah. The research uses an empirical juridical method with a socio-legal approach, employing interviews, observations, and documentation. The findings show that several factors hinder the regulation’s effectiveness, including low legal awareness, strong cultural traditions of mutual assistance, economic limitations, weak supervision, and insufficient government socialization. Many residents still perceive collecting donations on the road as an expression of social solidarity rather than a legal violation. However, supporting factors also exist, such as legal awareness among mosque administrators, the involvement of religious and local leaders, and the availability of legitimate fundraising mechanisms. From the siyāsah dustūriyyah perspective, the policy aligns with the principles of public welfare (al-maslahah al-‘āmmah) and the objectives of Islamic law (maqāṣid al-syarī‘ah), particularly the protection of life (ḥifẓ al-nafs) and property (ḥifẓ al-māl). The prohibition aims to prevent harm and uphold social order. Nonetheless, the regulation’s success requires a persuasive and humanistic approach, along with accessible legal fundraising alternatives. The study concludes that effective implementation depends on collaboration between government authorities, religious leaders, and the community to create a safer and more orderly social environment.